The unfinished leader : balancing contradictory answers to unsolvable problems - Dotlich, David L. (David Landreth), 1950-; Cairo, Peter C., 1948-; Cowan, Cade, 1972- (San Francisco, CA : Jossey-Bass, 2014)
"A leader's work is never done--not only because of long to-do lists and frequent meetings, but because every leader must confront complex dilemmas that don't have easy answers, and in fact may not have any right answer at all. In business, as in life, the most perplexing issues aren't like math problems with a single solution. They are paradoxes: situations in which there will never be a single right answer, and they will be familiar to anyone in a leadership role. Should your company prioritize long-term investments, or short-term profitability? Will your incenitive plan measure and reward the performance of individuals, or teams? How can you devote enough time and energy to both your family and your coworkers? The Unfinished Leader is a guide for managing through paradoxes like these to ensure success across the organization. Leaders must first learn to recognize the problems they won't be able to solve, and confront the obstacles--in their own heads and in the organizations where they work--that will push them (wrongly) towards finding single solutions that don't exist. Then, they must develop the mindsets and skills that enable them to balance contradictory directions, fulfill competing demands, and adapt their approach over time. Based on over 30 years of consulting work with senior executives, as well as a series of exclusive interviews with 100 CEOs and top leaders in a wide range of companies about the paradoxes they face, The Unfinished Leader provides tested advice. The authors include vivid stories highlighting leaders and the real-world challenges they've faced at organizations such as Avon, Nike, Colgate, DeutschePost DHL, Johnson & Johnson, and many more.No one can, or should, look for perfect solutions to impossible solutions. The Unfinished Leader will help leaders at all levels understand that their true task is to guide themselves and their teams through impossible-seeming, ongoing situations--and, by reconciling competing outcomes, drive lasting success for themselves and their teams"--
Introduction: Stepping up to complete leadership -- Puzzles and paradoxes -- Jumping over the line -- Obstacles to leadership -- The purpose mindset -- The reconciliation mindset -- The innovation mindset -- Scanning for the right paradox -- Scenario thinking -- Stakeholder mapping -- Dialogue for alignment -- Quelling conflict -- Developing yourself -- Conclusion: Managing personal and public paradoxes.
Includes bibliographical references and index.
Keywords: Leadership; Decision making; Work and family